(untitled) (LEGAL DIALOGICA, 2025)
This research was conducted with the aim of finding out and analyzing regulations related to the renewal of Building Use Rights (HGB) that are burdened with dependent rights and to understand the legal process that must be taken in the renewal of HGB which is still in the status of being burdened with dependent rights. This research is a type of normative legal research that is legal research that is carried out by researching literature materials or legal materials by taking issues from law as a norm system used, normative legal research makes the norm system the center of study. The results of the study show that the regulations regarding the renewal of the Building Use Rights (HGB) that are burdened with the right of remembrance are basically based on the explicit way in which the statute guarantees the integrity of the HGB are carried out. From a judicial point of view, the renewal is considered as a new right, until the Right of Suspension of the old HGB is declared null and void because the object of the guarantee no longer meets the principle of speciality. Therefore, although the subject matter and its object remain the same, the renewal of the HGB certification has been carried out to ensure the binding of the law through the Suspension Rights Guarantee Act (SKMHT) and the New Suspension Rights Act (APHT). The process of renewing the HGB which is still subject to the right of suspension also requires caution on the part of the detainer and the creditor. Renewal applications can only be made after the right has expired, as stipulated in PMNA/KBPN No. 9 of 1999. Therefore, as soon as the application is made, the creditor must ask the creditor to sign the SKMHT as a security clearance against the object of the guarantee, as an active act in the law of the object of the guarantee, as stipulated in Article 11 paragraph (2) of the Law on the Right of Defense (UUHT). Abstrak Penelitian ini dilakukan bertujuan untuk mengetahui dan menganalisis peraturan terkait pembaharuan Hak Guna Bangunan (HGB) yang dibebani hak tanggungan serta memahami proses hukum yang harus ditempuh dalam pembaharuan HGB yang masih berada dalam status dibebani hak tanggungan. Penelitian ini ialah jenis penelitian hukum normatif merupakan penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau Bahan Hukum dengan mengambil isu dari hukum sebagai sistem norma yang digunakan maka penelitian hukum normatif menjadikan sistem norma sebagai pusat kajian. Hasil penelitian menunjukkan bahwa peraturan mengenai pembaharuan Hak Guna Bangunan (HGB) yang dibeìbani hak tangguìngan pada dasarnya beìluìm meìngatuìr seìcara eìksplisit meìngeìnai statuìs jaminan keìtika dilakuìkan peìmbaharuìan HGB. Seìcara yuìridis, peìmbaharuìan dianggap seìbagai peìmbeìrian hak baruì, seìhingga Hak Tangguìngan atas HGB lama dinyatakan hapuìs kareìna objeìk jaminan tidak lagi meìmeìnuìhi asas speìsialitas. Oleìh kareìna ituì, meìskipuìn suìbjeìk dan objeìknya teìtap sama, peìmbaharuìan seìrtifikat HGB teìtap meìmbuìtuìhkan peìngikatan uìlang meìlaluìi Suìrat Kuìasa Meìmbeìbankan Hak Tangguìngan (SKMHT) dan Akta Peìmbeìrian Hak Tangguìngan (APHT) baruì uìntuìk meìnjamin peìrlinduìngan keìpeìntingan kreìditor. Proseìs huìkuìm peìmbaharuìan HGB yang masih dibeìbani hak tangguìngan juìga meìnuìntuìt keìhati-hatian dari pihak deìbitor mauìpuìn kreìditor. Peìngajuìan peìmbaharuìan hanya dapat dilakuìkan seìteìlah hak seìbeìluìmnya beìrakhir, seìbagaimana diatuìr dalam PMNA/KBPN No. 9 Tahuìn 1999. Oleìh kareìna ituì, seìbeìluìm peìngajuìan dilakuìkan, kreìditor peìrluì meìminta deìbitor meìnandatangani SKMHT seìbagai beìntuìk peìngamanan teìrhadap objeìk jaminan, seìrta seìcara aktif tuìruìt beìrtindak dalam uìpaya peìnyeìlamatan objeìk jaminan, seìbagaimana diatuìr dalam Pasal 11 ayat (2) huìruìf d dan k Undang-Undang Hak Tangguìngan (UUHT).